A speckle tracking echocardiographic study on right ventricular function in primary aldosteronism. Issue 11 (November 2020) - Chen, Yi-Lin; Xu, Ting-Yan; Xu, Jian-Zhong; Zhu, Li-Min; Li, Yan; Wang, Ji-Guang
Abstract : Objective: We investigated right ventricular function using speckle tracking echocardiography (STE) in patients with primary aldosteronism. Methods: Our study included 51 primary aldosteronism patients and 50 age and sex-matched primary hypertensive patients. We performed two-dimensional echocardiography to measure cardiac structure and function. We performed STE offline analysis on right ventricular four-chamber (RV4CLS) and free wall longitudinal strains (RVFWLS). Results: Primary aldosteronism patients, compared with primary hypertensive patients, had a significantly ( P ⩽ 0.045) greater left ventricular mass index (112.0 ± 22.6 vs. 95.8 ± 18.5 g/m 2 ) and left atrial volume index (26.9 ± 6.0 vs. 24.7 ± 5.6 ml/m 2 ) and higher prevalence of left ventricular concentric hypertrophy (35.3 vs. 12.0%), although they had similarly normal left ventricular ejection fraction (55–77%). Primary aldosteronism patients also had a significantly ( P ⩽ 0.047) larger right atrium and ventricle, lower tricuspid annular plane systolic excursion, and higher E/E't (the peak early filling velocity of trans-tricuspid flow to the peak early filling velocity of lateral tricuspid annulus ratio), estimated pulmonary arterial systolic pressure and right ventricular index of myocardial performance. On the right ventricular strain analysis, primary aldosteronism patients had a significantly ( P < 0.001) lower RV4CLS (−18.1 ± 2.5 vs. −23.3 ± 3.4%) and RVFWLS (−21.7 ± 3.7 vs. −27.9 ± 4.5%) than primary hypertensive patients. Overall, RV4CLS and RVFWLS were significantly ( r = −0.58 to −0.41, P < 0.001) correlated with plasma aldosterone concentration and 24-h urinary aldosterone excretion. After adjustment for confounding factors, the associations for RV4CLS and RVFWLS with 24-h urinary aldosterone excretion remained significant ( P < 0.001), with a standardized coefficient of −0.48 and −0.55, respectively. Conclusion: In addition to left ventricular abnormalities, primary aldosteronism patients also show impaired right ventricular function, probably because of hyperaldosteronism. Abstract : Supplemental Digital Content is available in the text